ACCESS TO COMMUNICATION PLANNING AND TRANSPORTATION MANAGEMENT TECHNOLOGY IN ASSESSMENT OF VEHICLE OPERATIONS IN PEKANBARU CITY'S, RIAU, INDONESIA - Yodiansyah, Hefri; Yuzalmi, Nanik; Zain, Irsyadi (International Journal of Research -GRANTHAALAYAH, 2018)
Management of leasing vehicles contributes significantly to amount of transportation driving the supply of fiduciaries fiduciary progress on the streets in Pekanbaru cities, Indonesian state. This development was caused by poor public transport supplies, urban leasing vehicles with fiduciary patterns and poor roads. The use of fiduciary vehicles for public transport in the city of Pekanbaru, Riau, Indonesia is associated with a high level of accidents both on the side of drivers, drivers and passenger’s fiduciary vehicles. This study investigates the social-economic impact of Pekanbaru city's most likely drivers in the Regional Government areas Indonesian state. Questionnaires were given to samples randomly selected 200 users’ area. Of the 200 questionnaires given, 183 questionnaires were received for analysis using the Statistical Package for Social Sciences (SPSS). The findings show that the majority of commercial fiduciary riders are adults between the ages of 31 and 40 years. Most (72.9%) are married and have sufficient educations. Selected male sexes, 78.6% of the 66 respondents Company guarantees full-time fiduciary vehicles and has operated for more than four years with a general policy pattern. The majority of riders are involved in business because of the urgent need to survive and defend their families. In addition, most motorists do not take the necessary precautions, they are earning consumers and family management even during working hours and this reason has been identified as the main cause of their carelessness.